Effects of prior knowledge and lesson outline on note taking and test scores - Olmos, Oscar Lasig (Education quarterly.)
This study sought to find the effects of two teaching strategies - the use of lesson outline and the activation of prior knowledge - on note taking and test scores. The relationship of between notes and test scores was also determined. Three intact classes of first year high school students were randomly assigned to three note taking environments prior to attending a videotaped lecture class. They were randomly assigned to prior knowledge environment, lesson outline environment, and control environment. A posttest was administered immediately after the lecture and the students' notes were collected and rated. The same test was administered to the students a week later, and they have reviewed their notes. Results indicated that prior knowledge and lesson outline do not necessary induce any specific note taking strategy. Note taking and review of notes are related to better test scores. Correlation tests showed that high test scores are associated with more notes.